Commodity cycle management in Latin America: The importance of resilience in face of vulnerability - Carrington, Sarah (2021)
In this paper we propose that commodity price cycles tend to have different effects on commodity exporting countries in Latin America depending on their level of vulnerability and institutional resilience to the commodity price cycle. In the investigation of the impact of commodity cycles on economic outcomes in commodity dependent economies, especially developing economies, most studies focus on the role of macroeconomic imbalances in their analysis of the resulting depth of economic downturn caused by commodity busts (de la Torre et al, 2020; Fernández, and Villar, 2014; Van der Ploeg and Venables, 2013; Clapp, 2009; Edwards, 2006; Edwards, 1985). However, this paper emphasizes that, while imbalances may contribute to the vulnerability of the economy, its resilience depends on its underlying structural and institutional characteristics. As part of that resilience, we suggest that the channel through which the resource earnings enter the economy and the way in which this income is managed determines the way commodity cycles can impact economic and social outcomes.